Innovative Drone-Based Methodologies for the Non-Invasive Assessment of Heritage Structures - Rubén Rodríguez Elizalde (Science and Technology: Developments and Applications Vol. 7, 2025)
This chapter presents an integrated inspection methodology for medieval masonry bridges utilizing advanced microtechnological tools, specifically aerial thermography and underwater drones, to achieve a non-invasive, comprehensive structural assessment of the Ponte de Vilanova (13th–14th century) in Allariz, Galicia. A multirotor drone equipped with infrared imaging facilitated the detection of thermal anomalies associated with moisture intrusion and efflorescence within the intrados and spandrel walls. Complementary underwater inspection via remotely operated vehicles (ROVs) enabled precise visualization and analysis of submerged foundation elements and riverbed morphology, confirming the structural stability of the central pier and ruling out active scouring or settlement processes. The combined use of aerial and aquatic drones minimized human risk, optimized inspection time, and reduced costs while preserving the monument’s integrity. The results underscore the potential of multisensorial drone-based inspections to redefine standard protocols in heritage conservation and structural health monitoring of ancient infrastructures.